Cation-mediated gelation of the fucose-rich polysaccharide FucoPol - Fialho, Letícia (2022)
FCT/MEC (UID/Multi/04378/2019). PEst-OE/AGR/UI0245/2014. POCI-01-0145-FEDER-007728 and POCI-01-0145-FEDER - 007265. SFRH/BD/140829/2018. SFRH/BPD/124612/2016.